Wind potential evaluation with urban morphology - A case study in Beijing. (October 2018) - Wang, Biao; Sun, Shuai; Duan, Minglei
Abstract: Wind energy is beneficial for the sustainable development of cities. With increasing new wind turbine technologies and CFD techniques, urban wind becomes to attract public attention while large-scale wind capacity installation is stabilizing. This work is trying to estimate wind energy within the angle of urban morphology. Seven different urban tissues were compared and analyzed with several relevant urban morphology parameters. Numerical simulations in CFD were undertaken to visualize the outcome of wind energy of each urban tissue. The results showed that the forms with lower floor area ratio usually have the higher wind potential density, and the forms with higher porosity usually have the higher wind potential density on unit of roof surface.